CRISPR technology in disease diagnosis - Bhure, Mahaling; Chavhan, Kailas; G K, Megha; Shinde, Shilpshri; Khan, Waqar; Patil, Archana; Chaudhari, Sandeep (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
CRISPR refers to Clustered regularly interspaced short palindromic repeats, these are palindromic sequences interspaced by viral nucleotide base pairs (spacers), which act as an adaptive immune system along with Cas proteins. Class 2 CRISPR-Cas systems are widely used for various applications due to the single Cas protein effector complex. It is widely used as a genome editing tool. In diagnostics, gRNA along with Cas proteins cuts a specific sequence with complementarity and fluorescence is produced by the reporter molecule. This can be widely used as a point-of-care diagnosis due to various advantages over other molecular techniques. In India CRISPR application is in the budding stage, it can be used as a potential tool to develop point-of-care diagnostic facilities to boost health services.
Keywords: CRISPR; Cas; gRNA; diagnosis; Genome editing